Unclassifiable short-rib thoracic dysplasia diagnosed using targeted gene panel sequencing - Erika Nakajima; Yuko Yokohama; Saori Sugiyama; Mio Taketazu; Kenrokuro Mitsube; Takahiro Yamada; Anna Hammarsjö; Giedre Grigelioniene; Gen Nishimura; Yoshio Makita (Human Genome Variation)
Abstract We report a case of a fetus with short-rib thoracic dysplasia (SRTD) with polydactyly that also presented with atypical severe acro-mesomelic ossification defects. Genetic analysis using massively parallel sequencing of a skeletal dysplasia panel revealed compound heterozygous variants in DYNC2H1. This clinical report highlights the challenges associated with diagnosing the diverse phenotypes in the SRTD group and emphasizes the importance of genetic surveillance with a targeted gene panel for accurate diagnosis.